LO042: Sonography in Hypotension and Cardiac Arrest (SHoC) - Hypotension: derivation of an evidence-based consensus algorithm for the integration of point of care ultrasound into resuscitation of hypotensive patients. (2nd June 2016) - Atkinson, P.; Bowra, J.; Milne, J.; Lambert, M.; Jarman, B.; Noble, V.; Lamprecht, H.; Lewis, D.; Harris, T.; Gangahar, R.; Stander, M.; Muhr, C.; et al.
Abstract : Introduction: Point of care ultrasound has become an established tool in the initial management of patients with undifferentiated hypotension. Current established protocols (RUSH, ACES, etc) were developed by expert user opinion, rather than objective, prospective data. We wished to use reported disease incidence to develop an informed approach to PoCUS in hypotension using a "4 F's" approach: Fluid; Form; Function; Filling.Methods: We summarized the incidence of PoCUS findings from an international multicentre RCT, and using a modified Delphi approach incorporating this data we obtained the input of 24 international experts associated with five professional organizations led by the International Federation of Emergency Medicine. The modified Delphi tool was developed to reach an international consensus on how to integrate PoCUS for hypotensive emergency department patients.Results: Rates of abnormal PoCUS findings from 151 patients with undifferentiated hypotension included left ventricular dynamic changes (43%), IVC abnormalities (27%), pericardial effusion (16%), and pleural fluid (8%). Abdominal pathology was rare (fluid 5%, AAA 2%). After two rounds of the survey, using majority consensus, agreement was reached on a SHoC-hypotension protocol comprising:A. Core: 1. Cardiac views (Sub-xiphoid and parasternal windows for pericardial fluid, cardiac form and ventricular function ); 2. Lung views for pleural fluid and B-lines for filling status; and 3. IVC views for filling status;B. Supplementary: Additional cardiac views; andC. Additional views (when indicated) including peritoneal fluid, aorta, pelvic for IUP, and proximal leg veins for DVT.Conclusion: An international consensus process based on prospectively collected disease incidence has led to a proposed SHoC-hypotension PoCUS protocol comprising a stepwise clinical-indication based approach of Core, Supplementary and Additional PoCUS views.